# Algebra

posted by .

4x^2-8x+3=5

4x² - 8x +3 - 5 = 0
4x²- 8x - 2 = 0
2x²- 4x -1 = 0

this is as far as I got. I am stuck and do not know what to do next can some one please help?

divide by two:
x²- 2x -1/2 = 0
Now add 1.5 to each side to complete the square:
x²- 2x -1/2 +1.5 = +1.5
(x-1)2=1.5
subtract 1.5 from each side
(x-1)2 -1.5 = 0

Now you have a difference of squares (1.5 is sqrt (3/2) squared..)
[x-1-sqrt3/2][x-1+sqrt3/2] = 0

divide by two:
x²- 2x -1/2 = 0
Now add 1.5 to each side to complete the square:
x²- 2x -1/2 +1.5 = +1.5
(x-1)2=1.5
subtract 1.5 from each side
(x-1)2 -1.5 = 0

Now you have a difference of squares (1.5 is sqrt (3/2) squared..)
[x-1-sqrt3/2][x-1+sqrt3/2] = 0

## Similar Questions

1. ### Maths

f:x -> (4x²-8x-21)/(x²-1) (a) Analyse (b) Sketch I'm struggling on (a) so I can't do (b) Here are my ideas/what I've got so far: (a)Domain, x is a set of real numbers; x can not equal 1 Asymptotes x=1, y=?
2. ### Calc

The slope of a curve at each point (x,y) is given by 4x - 1. Which of the following is an equation for this curve if it passes through the point (-2,3)?
3. ### calculus

Consider the function below. f(x) = 4x2 - 5x (a) Find f '(2). (b) Use the answer in part (a) to find an equation of the tangent line to the parabola y = 4x2 - 5x at the point (2, 6). y =
4. ### Algebra

What are the solutions of the quadratic equation below?
5. ### algebra

Put the equation in the form ax2 + bx + c = 0. Enter exponents using the caret ( ^ ). For example, you would enter 4x2 as 4x^2. 8-2x2=(x+2)2-7

1. What is the degree of the monomial 3x2y3?
7. ### maths

Write the system as a matrix equation and solve using inverses. x1 + 2x2 - x3 = -3 -2x1 - x2 + 3x3 = 0 -4x1 + 4x2 - x3 = -12 A. x1 = 2, x2 = -3, x3 = 1 B. x1 = 1, x2 = -2, x3 = 1 C. x1 = 1, x2 = -2, x3 = 0 D. x1 = 1, x2 = -3, x3 = …
8. ### Algebra

1. What polynomial has a graph that passes through the given points?
9. ### Algebra

Directions: Find the prime factors of the polynomials 1. a. 2a2 - 2b2 b. 6x2 - 6y2 c. 4x2 - 4 d. ax2 - ay2 e. cm2 - cn2 2. f. st2 - s g. 2x2 - 18 h. 2x2 - 32 i. 3x2 - 27y2 j. 18m2 - 8 3. k. 12a2 - 27b2 l. 63c2 - 7 m. x3 - 4x n. y3 …
10. ### Algebra 2

If f(x)= x2 + 2x - 6 and g(x)= 3x2 - 5x - 7, find f(x)-g(x). A) -2x2 - 3x + 1 B) -2x2 + 7x + 1 C) -2x2 - 3x - 13 <my choice D) 4x2 - 3x - 13

More Similar Questions